Diversidade sexual na Educação de Jovens e Adultos (EJA): limites e possibilidades da efetivação do direito à educação - Jerry Adriani da Silva (2016)
This thesis was constructed from the data collected during thecourse of doctoral research Sexual Diversity in Education ofYoung and Adults: limits and possibilities of education of therigght to effective. Such research aimed to understand thespecificities of / the students / LGBT's, the destabilization causedby the arrival of these / the students in groups of adult education,as well as mechanisms to prevent or invisibilized access,permanence and success of these / the school. Developed in twoschools, with the participation of two students, a teacher, ateacher, a coordinating one director and a manager to conductsemi-structured interviews and also eighty students whoanswered a questionnaire with forty-four questions. Tounderstand the movement of RME-BH that, despite its history ofprogress (and setbacks) in the design and construction of politicaland pedagogical practices, also deals with the challenges toconsider the specificities of the public attended, especially thatemerging from population LGBT, consultations were held withhistorical, documentary and digital collections of public sectors,recorded observations, scenes recordings, stories, testimonies andtestimonies in activities in the city Belo Horizonte by institutionsthat act in the cause LBGT's. The hypothesis investigated was thathomophobia is not only a barrier that must clearly be effectiveright to freedom of sexual orientation, but also the realization ofthe right to education of young, adult and elderly. Theorists suchas Bauman (2006), Borrillo (2010), Butler (2012 and 2015),Foucault (2010, 2014a and 2014b), Freire (2011 and 2014),Giddens (1993), Haddad (2007), Junqueira (2009), Lionço (2009),Louro (2007, 2009, 2014 and 2015), Miranda (2008), Prado eMachado (2008), Rubin (1989), Scott (1986), Soares (2005, 2008and 2011), Vianna (2012 and 2015) among others, contribute tothe argument that the EJA needs to meet the specific needs of itssubjects, based on the anti-homophobic perspective, which seeksthe realization of the rights to life, human dignity and the freeorientation sexual. The data revealed that homophobia is denialand violation of the rights and is present in the school routine,through issues such as indifference, mute, power relations,negotiations, progress, setbacks, consents, the revolts andalliances. Showed opportunities and coping strategieshomophobia, as well as the possible scenarios for building a lessviolent and exclusionary reality in schools. It was possible tocheck the progress of the proposed EJA surveyed; know,understand, record and analyze two pedagogical experiences ofadult education in the thematic LGBT's has highlighted; inventoryand analyze two educational practices aimed at promoting sexualdiversity recognition culture. And because we believe ourexploratory research, we suggest also topics for further research infuture research. Finally, the limits focus on the dominanthomophobic perspective and the possibilities are in strengtheningthe signs of building an anti-homophobic perspective in the EJA.